Magi : the labyrinth of magic. 35 - Otaka, Shinobu; Werry, John (Translator) (VIZ Media, LLC, 2019)
"Inside the Sacred Palace, Aladdin, Alibaba and Morgiana must face the Seven Dungeons of Sinbad--strange and deadly magical labyrinths where time flows backward and forward all at once! A confrontation with Sinbad was expected, but can they handle different versions of Sinbad at different times in his life?"--Page [4] of cover.